2017
DOI: 10.1007/s10147-016-1087-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of hyperfibrinogenemia in patients with esophageal squamous cell carcinoma

Abstract: Preoperative hyperfibrinogenemia was associated with inflammatory mediators, tumor progression, and poor survival in patients with esophageal squamous cell carcinoma. The absence of a decrease in plasma fibrinogen levels after surgical treatment may indicate the possibility of tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The binding complex could induce epithelial–mesenchymal transition to promote invasion and metastasis of ESCC cell [ 24 ]. Moverover, hyperfibrinogenemia was observed not only in our study, but also reported by Suzuki et al [ 25 ] and Kijima et al [ 26 ], and preoperative circulating Fib was an independent prognostic factor for ESCC [ 27 ]. Hence, we observed that AFR was superior to Fib to predict the survival of the ESCC patients.…”
Section: Discussionsupporting
confidence: 87%
“…The binding complex could induce epithelial–mesenchymal transition to promote invasion and metastasis of ESCC cell [ 24 ]. Moverover, hyperfibrinogenemia was observed not only in our study, but also reported by Suzuki et al [ 25 ] and Kijima et al [ 26 ], and preoperative circulating Fib was an independent prognostic factor for ESCC [ 27 ]. Hence, we observed that AFR was superior to Fib to predict the survival of the ESCC patients.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, 43 articles (44 studies) with 17,510 patients were included in the present meta-analysis. 5,6,9,10,14,16,18-21,23,2758…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 studies investigated the relationship between high fibrinogenemia and OS in ESCC. 5,16,18,23,27,34,39,49,52,57 A random-effects model was used to calculate the HR and 95% CI due to the severe heterogeneity (I 2 = 71%, P <0.001) among those studies. The pooled analysis indicated that fibrinogenemia was significantly related to a worse OS (HR 1.67; 95% CI 1.35, 2.07; P <0.001) (Supplement Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further for AA, plasma level of fibrinogen was also increased in upper gastrointestinal related malignancies including of gastric and esophageal carcinoma. The marker was associated with poor prognosis in malignant condition [ [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%